Balancing between extremes-Work in hospital‐at‐home - Heli Vaartio‐Rajalin; Kasanga Ngoni; Lisbeth Fagerström (Wiley, 2020)
Abstract Aim To describe HAH staff's perceptions about HAH care, including work structures, processes and outcomes. Design Cross‐sectional descriptive study of three HAH units in Finland. Methods Three focus group interviews of interprofessional staff members (N = 24) were analysed through thematic content analysis (COREQ). In addition, an audit visit was conducted at Guy's and St Thomas' @home service, the United Kingdom. Results The Finnish HAH staff perceived they were balancing between different extremes: the patient's and his/her near‐one's opinions and wishes, well‐being and integrity, the promotion of person‐centred care and own work safety, a deeper meaning for work and the need for further support. Both in Finland and the UK, patients were perceived to be satisfied with care and HAH was perceived to save hospital bed places.